The whale rider - Ihimaera, Witi, 1944- (New York : RAUPO, 1987)
As her beloved grandfather, chief of the Maori tribe of Whangara, New Zealand, struggles to lead in difficult times and to find a male successor, young Kahu is developing a mysterious relationship with whales, particularly the ancient bull whale whose legendary rider was their ancestor.
Includes glossary.
Keywords: Maori (New Zealand people) -- Fiction; Family life -- New Zealand -- Fiction; Grandfathers -- Fiction; Human-animal relationships -- Fiction; Kings, queens, rulers, etc. -- Fiction; Whales -- Fiction; New Zealand -- Fiction